Characterization of DLC-Coated and Uncoated Surfaces by New Directional Blanket Curvature Covering (DBCC) Method - Wolski, Marcin; Podsiadlo, Pawel; Stachowiak, Gwidon; Holmberg, K.; Laukkanen, A.; Ronkainen, H. (Springer, 2018)
Roughness and curvature of diamond-like carbon (DLC) surface coatings change with both scale and direction of a measurement. However, the changes are not detected by currently used standard parameters which are designed to work with isotropic surfaces at a single scale, thus providing only a limited information about multiscale and directional roughness and curvature. The problem of detailed roughness characterization of DLC-coated surfaces has been addressed in our previous work [Wolski et al. Multiscale characterization of 3D surface topography of DLC-coated and uncoated surfaces by directional blanket covering method. Wear 2017:388–389:47–56]. However, surface curvature description still remains an unresolved issue. To overcome this shortcoming, a directional blanket curvature covering (DBCC) method was developed. The method calculates curvature, peak and valley dimensions which quantify multiscale and directional curvature complexity of surface topography, peaks and valleys, respectively. Higher values of the dimensions represent higher complexity. In the current study, the DBCC method was used to analyse DLC-coated and uncoated bearing steel samples with increasing roughness and curvature. Its ability to discriminate between these two groups of surfaces was evaluated. Results showed that the method could detect minute changes in surface curvature at individual scales and directions. The method would be of interest to those who design wear-resistant systems and surfaces.